P3.154 Clonal spread of azithromycin resistant neisseria gonorrhoeae in canada (2014–2015). (8th July 2017) - Artin, I; Sawatzky, P; Lefebvre, B; Allen, V; Naidu, P; Hoang, L; Horsman, G; Mulvey, MR
Abstract : Introduction: Neisseria gonorrhoeae have acquired resistance to many antimicrobials including third generation cephalosporins and azithromycin, which are the current co-therapy recommended by the Canadian STI guidelines for gonorrhoea treatment. Minimum inhibitory concentrations (MIC) to azithromycin and molecular sequence types were determined for N. gonorrhoeae circulating in Canada. Methods: Between 2014 and 2015, N. gonorrhoeae strains isolated by Canadian provincial public health laboratories were submitted to the National Microbiology Laboratory (NML) (n=4, 720) for azithromycin MIC determination (resistance MIC ≥2.0 mg/L) by agar dilution. N. gonorrhoeae multi-antigen sequence typing (NG-MAST) was used for molecular typing. Results: Azithromycin resistance was identified in 3.3% (127/3, 809) and 4.7% (198/4, 190) of N. gonorrhoeae in 2014 and 2015, respectively, a significant increase since 2013 (p<0.001). MICs ranged from 2 to 16 mg/L. The most common sequence types identified in 2014 were ST10451 (n=40), ST10567 (n=38) and ST11765 (n=10). ST11765 is closely related to ST10451, differing by 1 bp in the por allele. In 2015, the prevalent sequence types were ST12302 (n=110), ST10451 (n=34) and ST9047 (n=23). ST10451, identified in Quebec, Ontario and Alberta, was newly identified in 2014 and also identified in 2015. ST10451 is related to ST1407 (differing by 1 bp in the por allele) which is an internationally-recognised epidemic strain, harbouring resistance to cephalosporins. ST12302 was newly recognised in 2015 and identified in two provinces, Quebec and Ontario. Conclusion: N. gonorrhoeae isolates in Canada show a significant increase in azithromycin resistance in 2014–2015. Azithromycin resistance in Canadian N. gonorrhoeae isolates are approaching the 5% level at which the WHO states an antimicrobial should be reviewed as an appropriate treatment. Continued surveillance of antimicrobial susceptibilities and sequence types of N. gonorrhoeae is necessary to identify clusters, inform treatment guidelines and mitigate the impact of resistant gonorrhoea.